2022
DOI: 10.3390/polym14040835
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Films Based on Starch from White, Red, and Black Rice to Food Application

Abstract: Packages from renewable sources have been the focus of many studies, due to the consumer needs for high-quality food, environmental concern related to the inadequate discard of packaging, low percentage of packaging recycling, and starch application by a viable method. Thus, this work aimed to develop bioactive packages based on white, red, and black rice starch and analyze the influence of macromolecule and plasticizer type, even its blends, on the characteristics of films. Films were characterized by color, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…In general, starch presents good properties for film formation [32][33][34][35], particulate systems [36,37], and gel formation [38][39][40][41][42], and is adequate for incorporating bioactive substances in controlled-release devices. An example of the process and its applications can be seen in Figure 2.…”
Section: Starchmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, starch presents good properties for film formation [32][33][34][35], particulate systems [36,37], and gel formation [38][39][40][41][42], and is adequate for incorporating bioactive substances in controlled-release devices. An example of the process and its applications can be seen in Figure 2.…”
Section: Starchmentioning
confidence: 99%
“…This provided the films with antioxidant activity, and showed a shift on FTIR spectra in the region associated with hydroxyl groups, thus indicating the importance of this functional group in the bonding between the starch matrix and the bioactive compounds. Da Silva, Velasco, and Fakhouri [33] demonstrated that, depending on the starch source, the film can demonstrate antioxidant properties itself, since films produced from different types of rice showed the presence of phenolic compounds.…”
Section: Packaging Applicationsmentioning
confidence: 99%
“…Conventional corn starch has long been used in mixtures with PLA and PBAT for the development of films for food packaging, due to its renewable, cheap, ecological, biodegradable and biocompatible characteristics [14][15][16]. Several botanical sources have been investigated to develop packaging, the native starch of babassu mesocarp appears as a potential candidate for future investigations, since it is widely cultivated in Brazil [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Due to its higher concentration of lysine (~4%), it is highly digestible, up to 93%. Additionally, rice contains minerals such as calcium (Ca), magnesium (Mg) and phosphorus (P), copper (Cu), iron (Fe), manganese (Mn) and zinc (Zn) [1][2][3][4][5][6][7].…”
mentioning
confidence: 99%
“…It offers numerous health benefits, including natural antioxidants, anti-inflammatory properties, lipid oxidation reduction, blood sugar level regulation, and anti-cancer effects. Black rice is particularly rich in phytochemicals, anthocyanin color, protein, and vitamins, making it well-regarded for its antioxidant capacity, which is essential for memory improvement and immune system support [5][6][7][8][9][10].…”
mentioning
confidence: 99%